The Creative Visual Analysis : Postmodern Visual Communication in the Black Hawk Down Headline Article on Jawa Pos - Sukirno, Zakaria Lantang; Irfan, Edoardo; Alma Mandjusri, Alma; Setyowati Karyaningtyas, Setyowati (Electronic Journal of Social and Political Sciences (E-SOSPOL), 2025)
Jawa Pos, on Saturday, February 1, 2025, published an article headlined "Black Hawk Down." The article covered the incident involving a Black Hawk helicopter colliding with American Airlines flight 5342 in Washington, D.C., USA, on Wednesday, January 29, 2025. The article's title and illustrations evoked nostalgia for the film Black Hawk Down (2001). From a postmodern perspective, this Jawa Pos article is interesting to examine in terms of how postmodernism was depicted using creative visual analysis. This research aimed, firstly, to describe the symbolic visualization of postmodernism in print media. Secondly, it aimed to methodologically significantly determine and popularize creative visual analysis as a data analysis technique for visual media objects. The research method employed a qualitative descriptive approach. The analytical technique used was creative visual analysis with art-based analysis interpretation. The research finding and interpretation described that the postmodern elements in the visual communication of the Jawa Pos’ headline article were inter-visually, nostalgia, and playfulness.